Computational Prediction of Phosphoinositide Binding to Hyperpolarization-Activated Cyclic-Nucleotide Gated Channels - Claveras Cabezudo, Ainara; Feriel Khoualdi, Asma; D’Avanzo, Nazzareno (Frontiers in Physiology, 2022)
Protein-lipid interactions are key regulators of ion channel function. Numerous ion channels, including hyperpolarization-activated cyclic-nucleotide gated (HCN) channels have been shown to be regulated by phosphoinositides (PIPs), with important implications in cardiac and neuronal function. Specifically, PIPs have been shown to enhance HCN activation. Using computational approaches, we aim to identify potential binding sites for HCN1-PIP interactions. Computational docking and coarse-grained simulations indicate that PIP binding to HCN1 channels is not well coordinated, but rather occurs over a broad surface of charged residues primarily in the HCN-domain, S2 and S3 helices that can be loosely organized in 2 or 3 overlapping clusters. Thus, PIP-HCN1 interactions are more resembling of electrostatic interactions that occur in myristoylated anlanine-rich C kinase substrate (MARCKS) proteins, than the specifically coordinated interactions that occur in pleckstrin homology domains (PH domains) or ion channels such as inward rectifier potassium (Kir) channels. Our results also indicate that phosphatidylinositol (PI) interactions with HCN1 are even lower affinity, explaining why unphosphorylated PI have no effect on HCN1 activation unlike phosphorylated PIPs.